Real social analytics: A contribution towards a phenomenology of a digital world. (18th February 2016) - Couldry, Nick; Fotopoulou, Aristea; Dickens, Luke
Abstract: This article argues against the assumption that agency and reflexivity disappear in an age of 'algorithmic power' (Lash 2007). Following the suggestions of Beer (2009), it proposes that, far from disappearing, new forms of agency and reflexivity around the embedding in everyday practice of not only algorithms but also analytics more broadly are emerging, as social actors continue to pursue their social ends but mediated through digital interfaces: this is the consequence of many social actors now needing their digital presence, regardless of whether they want this, to be measured and counted. The article proposes 'social analytics' as a new topic for sociology: the sociological study of social actors' uses of analytics not for the sake of measurement itself (or to make profit from measurement) but in order to fulfil better their social ends through an enhancement of their digital presence. The article places social analytics in the context of earlier debates about categorization, algorithmic power, and self‐presentation online, and describes in detail a case study with a UK community organization which generated the social analytics approach. The article concludes with reflections on the implications of this approach for further sociological fieldwork in a digital world.